Influence of starting strategy on cycling time trial performance in the heat - Abbiss, C. R.; Pfeiffer, J. J.; Wall, B. A.; Martin, D. T.; Laursen, P. B. (International Journal of Sports Medicine, 2009)
The purpose of this study was to determine the influence of starting strategy on time trial performance in the heat. Eleven endurance trained male cyclists (30±5 years, 79.5±4.6 kg, VO2max 58.5±5.0 ml.kg.-1 min-1) performed four 20-km time trials in the heat (32.7±0.7°C and 55% relative humidity). The first time trial was completed at a self-selected pace (SPTT). During the following time trials, subjects performed the initial 2.5-km at power outputs 10% above (10% ATT), 10% below (10% BTT) or equal (ETT) to that of the average power during the initial 2.5-km of the self-selected trial; the remaining 17.5-km was self-paced. Throughout each time trial, power output, rectal temperature, skin temperature, heat storage, pain intensity and thermal sensation were taken. Despite significantly (P<0.05) greater power outputs for 10% BTT (273±45W) compared with the ETT (267±48W) and 10% ATT (265±41W) during the final 17.5-km, overall 20-km performance time was not significantly different amongst trials. There were no differences in any of the other measured variables between trials. These data show that varying starting power by ±10% did not affect 20 km time trial performance in the heat.